Atriadops macula (Wiedemann) inhabiting the canopy: the first record of Nemestrinidae (Diptera) in the Amazon Basin - Rafael, José A.; Marques, Dayse W. A.; Limeira-De-Oliveira, Francisco (Zootaxa, 2020)
This is the first record of the family Nemestrinidae in the Amazon Basin, based on three females identified as Atriadops macula (Wiedemann, 1824). The specimens were collected in the canopy using flight interception traps. This species was previously known to inhabit understory open areas. The canopy, the new habitat record, is an open area stratum with higher insolation, higher temperature and less humidity. As the adults of A. macula have the mouthparts greatly reduced, they probably do not feed and their occurrence in the canopy probably is more likely related to the distribution of their hosts as well as the environmental factors.